2015
DOI: 10.1021/acs.estlett.5b00090
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for Identifying Organic Compounds of Concern in Hydraulic Fracturing Fluids Based on Their Mobility and Persistence in Groundwater

Abstract: We developed a screening framework for identifying organic components of hydraulic fracturing fluid with increased probability of exposure via groundwater based on mobility, persistence, toxicity, and frequency of use. Of 996 organic fracturing fluid compounds identified by the U.S. Environmental Protection Agency and FracFocus for four states, data were available to perform an initial screening of 659 compounds for sufficient mobility and persistence to reach a water well under fast and slow groundwater trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 33 publications
(76 reference statements)
2
96
1
1
Order By: Relevance
“…Although the total number of cases of thermogenic stray gas is relatively low, it is clear from COGCC complaint reports that individual cases pose significant safety, financial, emotional, and health risks to landowners (SI Appendix). Evaluation, mitigation, and prevention of these impacts should remain an ongoing high priority (32,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Although the total number of cases of thermogenic stray gas is relatively low, it is clear from COGCC complaint reports that individual cases pose significant safety, financial, emotional, and health risks to landowners (SI Appendix). Evaluation, mitigation, and prevention of these impacts should remain an ongoing high priority (32,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…Based on investigations of mobility, persistence, and toxicity, Rogers et al . [] concluded that 15 commonly used HF chemicals can travel over a setback distance of 94 m, at concentrations >10% of injected concentrations. Nine of these 15 chemicals have either a maximum contaminant level or health assessment information associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…While many of the additives are biodegradable and/or have low toxicity, approximately one-third of the chemicals studied by Stringfellow et al [2014] do not have toxicity data, some are toxic, and some are known or suspected carcinogens. Based on investigations of mobility, persistence, and toxicity, Rogers et al [2015] concluded that 15 commonly used HF chemicals can travel over a setback distance of 94 m, at concentrations >10% of injected concentrations. Nine of these 15 chemicals have either a maximum contaminant level or health assessment information associated with them.…”
Section: Introductionmentioning
confidence: 99%
“…(v) Toxicity measurements [79][80][81] or estimates, exposure models, 82 and population data could be appended, akin to the EPA's Risk Screening Environmental Indicators (RSEI) model, 83 using FracFocus ingredient disclosures and input in lieu of the Toxic Release Inventory (TRI).…”
Section: Discussionmentioning
confidence: 99%